Carbamazepine‐ and oxcarbazepine‐induced hyponatremia in people with epilepsy. (24th May 2017) - Berghuis, Bianca; van der Palen, Job; de Haan, Gerrit‐Jan; Lindhout, Dick; Koeleman, Bobby P. C.; Sander, Josemir W.; ,
Summary: Objective: To ascertain possible determinants of carbamazepine (CBZ)– and oxcarbazepine (OXC)–induced hyponatremia in a large cohort of people with epilepsy. Methods: We collected data on serum sodium levels in people with epilepsy who were attending a tertiary epilepsy center while on treatment with CBZ or OXC. We defined hyponatremia as Na+ ≤134 mEq/L and severe hyponatremia as Na+ ≤128 mEq/L. Results: We identified 1, 782 people who had used CBZ (n = 1, 424) or OXC (n = 358), of whom 50 were treated with both drugs. Data on sodium level measurements were available in 1, 132 on CBZ and in 289 on OXC. Hyponatremia occurred in 26% of those taking CBZ and 46% of those taking OXC. This was severe in 7% in the CBZ group and 22% in the OXC group. Hyponatremia was symptomatic in 48% and led to admissions in 3%. Age over 40 years, high serum levels of CBZ and OXC, and concomitant use of other antiepileptic drugs were the main risk factors for hyponatremia in both treatment groups. Female patients on OXC were at a higher risk than male patients of hyponatremia. The risk of hyponatremia on CBZ was significantly associated with the risk of hyponatremia on OXC within a subgroup that used both drugs consecutively. Significance: Hyponatremia is a common problem in people taking CBZ or OXC. Regular ascertainment of sodium levels in those taking either drug is recommended and results should be acted on.